1990
DOI: 10.1104/pp.92.2.506
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Inhibits α-Amylase Synthesis in Barley Aleurone without Inhibiting the Activity of Endoplasmic Reticulum Marker Enzymes

Abstract: The effects of heat shock on the synthesis of a-amylase and on the membranes of the endoplasmic reticulum (ER) of barley (Hordeum vulgare) aleurone were studied. Heat shock, imposed by raising the temperature of incubation from 250C to 400C for 3 hours, inhibits the accumulation of a-amylase and other proteins in the incubation medium of barley aleurone layers treated with gibberellic acid and Ca2 . When ER is isolated from heat-shocked aleurone layers, less newly synthesized a-amylase is found associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…A notable exception is vanadate-sensitive ATPase activity, a marker enzyme for the plasma membrane, which had a shoulder of activity in the ER microsome fractions. Heat shock decreased the buoyant density of ER microsomes, which is consistent with the observations of Sticher et al (1990).…”
Section: Lncubation With Ga Lncreases the Amount Of Unsaturated Fattsupporting
confidence: 90%
See 3 more Smart Citations
“…A notable exception is vanadate-sensitive ATPase activity, a marker enzyme for the plasma membrane, which had a shoulder of activity in the ER microsome fractions. Heat shock decreased the buoyant density of ER microsomes, which is consistent with the observations of Sticher et al (1990).…”
Section: Lncubation With Ga Lncreases the Amount Of Unsaturated Fattsupporting
confidence: 90%
“…Heat-shocked aleurone cells may therefore be able to continue the secretion of proteins as long as secretory proteins enter the endomembrane pathway. Sticher et al (1990) demonstrated that ER-associated Ca2+ transport and Cyt c reductase activities of barley aleurone cells are not diminished during heat shock, indicating that these ER functions are not heat labile. In contrast, heat shock does not affect the synthesis of phytohemagglutinin in heat-shocked soybean cotyledons, but it does stop the posttranslational processing of this protein in the ER (Chrispeels and Greenwood, 1987).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…iB) and homogenates of whole tissue (Fig. 1 B) Enzyme and Protein Assays a-Amylase was assayed using the standard I2KI procedure (15) and latent IDPase as described previously (25). The tonoplast fraction was identified using the vacuolar membrane marker TP 25 (11) and a nitrate-sensitive ATPase activity (6).…”
Section: Resultsmentioning
confidence: 99%